MENGEMBANGKAN KECERDASAN EMOSI ANAK MELALUI PERMAINAN BALOK DI TK DHARMA WANITA PERSATUAN II KARANGANYAR - Yeti Sukesi; Umi Thohiroh Tauchidiyah (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2021)
The formulation of the problem in this research is how to develop children's emotional intelligence through block games at Dharma Wanita Persatuan II Kindergarten in Karanganyar? The purpose of this research is to describe the development of children's emotional intelligence through block games at Dharma Wanita Persatuan II Kindergarten in Karanganyar. This research uses classroom action research. The results showed that children's emotional intelligence can be increased through block games. It is proven that in cycle I, the development of children's emotional intelligence through block games is still lacking, as the indicators developed (controlling emotions, self-confidence, recognizing emotions, showing emotions and being patient) are still lacking. In cycle II, children's abilities have increased, namely children are able to control emotions, have self-confidence, recognize emotions, show emotions and be patient. Thus, the block game at Dharma Wanita Persatuan II Karanganyar Kindergarten can develop children's emotional intelligence.